Rail Transportation 2006
DOI: 10.1115/imece2006-13212
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Analyses for Railroad Tank Car Head Puncture Resistance

Abstract: This paper describes engineering analyses to estimate the forces, deformations, and puncture resistance of railroad tank cars. Different approaches to examine puncture of the tank car head are described. One approach is semi-empirical equations to estimate the velocity at which puncture is expected to occur. Other approaches apply elastic-plastic finite element analysis. The results from these approaches are compared with experimental data from impact tests, and are shown to provide reasonable estimates of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Moreover, the force-indentation data from the full-scale tests and the results from the FEA (refer to Figure 5) suggest that n, the exponent in equation (6), is equal to ½. Applying this value to equations (8) and (9) further suggests that the maximum indentation is proportional to the impact velocity raised to the 4/3 power, and that the maximum force is proportional to the impact velocity raised to the 2/3 power.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the force-indentation data from the full-scale tests and the results from the FEA (refer to Figure 5) suggest that n, the exponent in equation (6), is equal to ½. Applying this value to equations (8) and (9) further suggests that the maximum indentation is proportional to the impact velocity raised to the 4/3 power, and that the maximum force is proportional to the impact velocity raised to the 2/3 power.…”
Section: Appendixmentioning
confidence: 99%
“…Approved for public release; distribution is unlimited. Dynamic, nonlinear (i.e., elastic-plastic material behavior with large deformations) finite element analysis (FEA) models have been developed to examine the structural response of tank cars under generalized head [6] and shell [7] impact scenarios. Specifically, the FEA models are used to calculate impact force as a function of indentation, or force-indentation characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…The comparisons indicated that the estimates for puncture velocity tend to be conservative [6][7]. In this context, conservative means that puncture is expected to occur at velocities greater than the calculated value.…”
Section: Figure 1: Generalized Tank Car Head Impact Scenariomentioning
confidence: 99%
“…Results from FEA models were presented previously in reference [5], but the effects of This material is declared a work of the U.S. Government and is not subject to copyright protection in the United States. Approved for public release; distribution is unlimited.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the focus of the research has shifted to also maintain tank integrity under rare and extreme circumstances such as impact loading during accidents. Previous research has been conducted by the Volpe Center to examine tank car impacts to the head [5] and the side or shell [6,7] of tank cars. Such failures occur from collisions with objects such as couplers and wheels from adjacent cars, broken rails, etc.…”
Section: Introductionmentioning
confidence: 99%